PENGENALAN KONSEP PERKALIAN PADA ANAK USIA DINI MENGGUNAKAN MEDIA BAHAN ALAM: INTRODUCTION TO THE CONCEPT OF MULTIPLICATION IN EARLY CHILDREN USING NATURAL MATERIALS - Lathipah Hasanah; Nadine Bong; Naila Fakhira; Alya Shafira; Catur Wulandari (incrementapedia, 2022)
Mathematics is the science of numbers, the relationship between numbers, and the operational procedures used in solving problems concerning numbers. Mathematics comes from the Latin word mathematica, which was originally taken from the Greek word mathematic, which means "relating to learning". This word has the root word mathema which means knowledge, science. Mathematics is concerned with structured ideas whose relationships are arranged logically. This means that mathematics is very abstract. That is with regard to abstract concepts and deductive reasoning. Mathematics learning in early childhood is given in stages beginning with counting objects or experiences of real events experienced by children in everyday life and based on children's observations. The introduction of mathematical concepts for children is to use simple language, so that children can easily understand what has been conveyed by the teacher. The introduction of early childhood mathematics is adjusted to the level of children's mental development and when children learn to count, in teaching children to learn to count, it can be started with simple things such as: recognizing numbers when blowing out birthday candles, counting the amount of food they will eat. , counting fruit in the fridge, counting by listening to songs, counting when wearing shoes, counting through toys, through apps, and through movies. This journal uses a literature review research method approach or literature study, which contains theories relevant to research problems. The results showed that learning mathematics using existing media in the children's environment made it easier for children to learn to count and children become more interested in learning mathematics.